Role of Anterior Cervical Discectomy and Titanium Cage Fusion in patients with Degenerative Cervical Spine Disease (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional and radiological outcome of anterior cervical discectomy and titanium cage fusion in patients with degenerative cervical spine disease.Methods: This descriptive study was conducted in Orthopaedic and spine unit Ziauddin Hospital Karachi from 23rd January 2017 to 23rd March 2022.All patients with painful single level degenerative cervical spine disease fulfilling the inclusion criteria were treated with anterior cervical discectomy and titanium cage fusion. Post operative functional outcome at one year follow up was assessed with Neck Disability Index (NDI) score and compared with pre operative score. The pre operative and post operative quality of life and pain intensity was measured with EQ-5D-5L score and Visual Analogue Scale (VAS) respectively. Post operative radiographs were assessed for fusion, cage subsidence and kyphosis.Results: We operated 38 patients of degenerative cervical spine disease with anterior cervical discectomy and titanium cage fusion. The mean NDI improved from a pre-operative score of 43/60 (moderate disability) to 21/60(mild disability) post operatively(p